THE POSITION OF RIGHTS AND CITIZENS IN THE PERSPECTIVE OF THE INDONESIAN CONSTITUTION ANALYSIS OF THE 1945 CONSTITUTION - Evan Nurfauzan Mulyawan; Atsiilah Fara Niccu; Maida Salma; Suci Setia Rahayu; A'ah Mar'atus Solikah (CV. ADIBA AISHA AMIRA, 2026)
Indonesia’s constitutional order is founded on the principle of a state governed by law, in which citizens’ rights and obligations form the core of the relationship between the state and its people. The 1945 Constitution provides normative recognition and legal guarantees for fundamental rights while simultaneously prescribing constitutional duties necessary to maintain public order and collective responsibility. In practice, however, the implementation of these rights and duties faces normative ambiguities and practical challenges, including uneven legal awareness and inconsistent enforcement. This study aims to analyze the constitutional position of citizens’ rights and obligations based on the 1945 Constitution and to clarify their balanced design within Indonesia’s constitutional framework. The research employs normative juridical methods using constitutional, statutory, and conceptual approaches supported by relevant legal doctrines. The findings demonstrate that the Constitution establishes a principled balance between rights and obligations through legal guarantees, proportional limitations, and the state’s duty to respect, protect, and fulfill constitutional rights. At the same time, citizens are bound by duties that ensure legal order and social harmony.